2022
DOI: 10.3390/beverages8010017
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Microbial Targets for Treatments to Preserve Fresh Carrot Juice

Abstract: Fresh carrot juice presents nutritional and organoleptic qualities which have to be preserved. However, it is a fast perishable beverage, and its low-acidic pH promotes the development of foodborne pathogens and spoilage microorganisms. This study aims to assess the modification and variability of physicochemical and microbial indicators during storage of carrot juice, and to isolate and select microorganisms to be used as promoters of spoilage to quantify the effect of preservation treatments. To achieve that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In some cases, adaptation may occur and for that reason a full screening is officially recommended [ 56 ]. However, such a result was not observed in our study, thus implying an extended shelf life for the novel juices (typically 1–5 days) [ 58 ], a feature that could surely be exploited by the food industry.…”
Section: Resultsmentioning
confidence: 60%
“…In some cases, adaptation may occur and for that reason a full screening is officially recommended [ 56 ]. However, such a result was not observed in our study, thus implying an extended shelf life for the novel juices (typically 1–5 days) [ 58 ], a feature that could surely be exploited by the food industry.…”
Section: Resultsmentioning
confidence: 60%
“…The numbers of Enterobacteriaceae and E. coli were determined according to ISO 21528-2/2017 [ 65 ] and ISO 4832/2006 [ 66 ], respectively. From the dilutions made, 1 mL of sample was taken and inoculated on Petrifilm 3M Rapid E. coli /Coliform Count Plate and Petrifilm 3M Enterobacteriaceae, and then incubated at 37 °C for 24 h [ 67 , 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the increase in the Enterobacteriaceae count observed after 4 days of storage was less significant, despite the signs of microbial spoilage of the juice. Leneveu-Jenvrin et al [42] observed that the Enterobacteriaceae count increased significantly between day 3 and day 7 of storage; however, there was little to no change between day 7 and day 10 of storage.…”
Section: Microbiome Analysesmentioning
confidence: 97%
“…Leneveu-Jenvrin et al [42] observed the total Enterobacteriaceae count at over 5 log CFU/mL for freshly prepared pure carrot juice, and over 5.5 log CFU/mL for commercial fresh carrot juice. They also noticed that, during 3 days of storage, the total Enterobacteriaceae count in lab-made carrot juice was stable, while, in commercial carrot juice, it increased by almost one logarithmic cycle.…”
Section: Microbiome Analysesmentioning
confidence: 99%
See 1 more Smart Citation